Answer: x = 1/5 and y= -7/5
Step-by-step explanation: Let's solve your system by elimination.
Multiply the first equation by -3,and multiply the second equation by 1.
-3 (x - 2y = 3)
1 (3x - y = 2)
Becomes:
-3x + 6y = -9
3x -y = 2
Add these equations to eliminate x:
5y = -7
Then solve 5y = -7
5y/7 = -7/5
y = -7/5
Now that we‘ve found y, let’s plug it back in and solve for x.
Write down an original equation:
x - 2y = 3
Substitute -7/5 for y in x - 2y = 3:
x - 2 (-7/5) = 3
x + 14/5 = 3
x 14/5 + -14/5 = 3 + -14/5 (Add (-14)/5 to both sides)
x = 1/5
Answer:
x = 1/5 and y = -7/5